Comparison between Hospital Brand Images of Public versus that of Private Hospitals in Kinondoni – Dar es Salaam, Tanzania - Machumani, Machumani Kiwanga; Mohamed, Salum Soud (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The study compared the brand image of public and private hospitals in Kinondoni Municipal Council, Dar es Salaam, Tanzania. The study used a sample size of 384 respondents. Quantitative analysis was used to analyze data using SPSS whereby descriptive analysis and compared mean test was used in interpreting the study results. The study revealed that people didn't have a good idea of how well-known, well-equipped, and comfortable public hospitals are. Public hospitals don't have good enough reputation for people to trust them and for doctors to act in the right way. Concerning the brand image of the services offered by private hospitals in Kinondoni Municipal, it was said that there was an inadequate image of advanced medical equipment, facilities, a comfortable environment, trusting doctors, and an inadequate attitude on advanced medical equipment. The study recommends that in order to improve patient loyalty both public and private hospitals need to strengthen communication between their patients and service providers.